2013
DOI: 10.1186/1471-2229-13-36
|View full text |Cite
|
Sign up to set email alerts
|

The ArabidopsisAt1g30680 gene encodes a homologue to the phage T7 gp4 protein that has both DNA primase and DNA helicase activities

Abstract: BackgroundThe Arabidopsis thaliana genome encodes a homologue of the full-length bacteriophage T7 gp4 protein, which is also homologous to the eukaryotic Twinkle protein. While the phage protein has both DNA primase and DNA helicase activities, in animal cells Twinkle is localized to mitochondria and has only DNA helicase activity due to sequence changes in the DNA primase domain. However, Arabidopsis and other plant Twinkle homologues retain sequence homology for both functional domains of the phage protein. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 46 publications
(95 reference statements)
2
59
1
Order By: Relevance
“…This contrasts with the situation in bacteria, where ppGpp inhibits proliferation by directly targeting DNA primase, the enzyme that initiates DNA replication (Dalebroux and Swanson, 2012). The inability of ppGpp to inhibit DNA replication in Arabidopsis chloroplasts could be explained by the recent observation that plants lack bacteria-like DNA primases and that chloroplast DNA replication is instead likely to be primed by a eukaryotic TWINKLE homolog (Diray-Arce et al, 2013). Importantly, we also found that, despite the increased chloroplast number, the percentage of total cell volume occupied by chloroplasts was significantly lower than that in wild-type plants ( Figure 2C).…”
Section: Results Ppgpp Regulates Global Chloroplast Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…This contrasts with the situation in bacteria, where ppGpp inhibits proliferation by directly targeting DNA primase, the enzyme that initiates DNA replication (Dalebroux and Swanson, 2012). The inability of ppGpp to inhibit DNA replication in Arabidopsis chloroplasts could be explained by the recent observation that plants lack bacteria-like DNA primases and that chloroplast DNA replication is instead likely to be primed by a eukaryotic TWINKLE homolog (Diray-Arce et al, 2013). Importantly, we also found that, despite the increased chloroplast number, the percentage of total cell volume occupied by chloroplasts was significantly lower than that in wild-type plants ( Figure 2C).…”
Section: Results Ppgpp Regulates Global Chloroplast Functionmentioning
confidence: 97%
“…This is likely to be because, in plants, the cyanobacterial DNA primase has been replaced by a eukaryotic TWINKLE homolog (Diray-Arce et al, 2013). This event has important implications for chloroplast evolution because it resulted in the transfer of the control of replication and division from the chloroplast to the nucleocytoplasmic compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Whether there are replication checkpoints has not been documented, and it is not known whether replication of the two mtDNA strands is coupled or independent. The former is possible because the organellar replicative helicase has intrinsic DNA primase activity (Diray-Arce et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2a) [27]. The ATH gene product was expressed, isolated, and found to be a robust DNA helicase, able to unwind double stranded DNA [16,17]. ATH was also shown to have primase activity, although it was not as efficient as gp4 [16].…”
Section: Resultsmentioning
confidence: 99%
“…This protein has been cloned, expressed, and shown to have both DNA primase and helicase activities [16,17]. Although ATH appears to have some primase activity, it is likely not sufficient enough to simultaneously replicate both the leading and the lagging strands.…”
Section: Introductionmentioning
confidence: 99%